PSVII-32 Profiling peripheral microRNA in normal- versus over-conditioned dairy cows during dry-off and early lactation. (7th December 2018) - Urh, C; Schuh, K; Zamarian, V; Webb, L; Lecchi, C; Alaedin, M; Sadri, H; Ghaffari, M; Dusel, G; Koch, C; Trakooljul, N; Wimmers, K; et al.
Abstract: Circulating microRNA (miRNA) may provide insight into physiological or pathophysiological statuses and the underlying metabolic pathways. Our objective was to characterize the miRNA serum profile in dairy cows with normal versus high body condition score (BCS). Thirty pluriparous Holstein cows were preselected 15 wk before calving for either high or normal BCS (HBCS > 3.75, NBCS < 3.5 at calving). A comparative analysis of miRNA extracted from serum obtained at d -49 and +21 relative to calving (three pools with five cows each per time point and group) was done by miRNA sequencing to identify miRNA that were different (false discovery rate < 0.05) between groups or time points. The expression of five differentially expressed (DE-) miRNA (miR-30a, miR-122, miR-148a, miR-455, and miR-1306) was validated in all individual samples via qPCR including additional time points (d -7, +7, +84). Differences between groups and time points were tested on Box-Cox-transformed data using the linear mixed model (SPSS). The expression of all five DE-miRNA was consistently lowest at d -7 and/or +7 (P < 0.05). Group differences were also observed, except for miR-30a and miR-1306. Changes with time were mostly parallel in both groups, only for miR-148a a group by time interaction was evident (P < 0.02) with lesser expression in NBCS than in HBCS cows at d -49, and reversed differences at d +21. For the miRNA investigated herein, the functional roles as well as the alterations in expression related to diseases are partly known, e.g. miR-148a regulating LDL receptor and ATP-binding cassette transporter (ABCA1) expression (Goedeke et al. 2015), and miR-122 being decreased in serum of fatty liver patients (Miyaki et al. 2014). Future research should address whether these findings can be confirmed in ruminants, in particular in the context of the adaptation to lactation in dairy cows.